2010
DOI: 10.1039/c002147d
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic platform for complete mammalian cell culture

Abstract: We introduce the first lab-on-a-chip platform for complete mammalian cell culture. The new method is powered by digital microfluidics (DMF), a technique in which nanolitre-sized droplets are manipulated on an open surface of an array of electrodes. This is the first application of DMF to adherent cell culture and analysis, and more importantly, represents the first microfluidic platform capable of implementing all of the steps required for mammalian cell culture-cell seeding, growth, detachment, and re-seeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
196
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(199 citation statements)
references
References 34 publications
(35 reference statements)
1
196
2
Order By: Relevance
“…At 4 h after seeding in microgels, viability was B100%; while at 24 h after seeding, viability was B80%. The effects of electrostatic actuation on cell health were not explicitly evaluated here, but previous studies with 2D adherent or suspension cell culture have reported no or negligible effects on cell viability/morphology 24,45 or gene expression 46 when compared with non-actuated cells (as the electrical field drops across the insulating layer rather than droplets containing cells). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At 4 h after seeding in microgels, viability was B100%; while at 24 h after seeding, viability was B80%. The effects of electrostatic actuation on cell health were not explicitly evaluated here, but previous studies with 2D adherent or suspension cell culture have reported no or negligible effects on cell viability/morphology 24,45 or gene expression 46 when compared with non-actuated cells (as the electrical field drops across the insulating layer rather than droplets containing cells). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using EWOD, they were able to demonstrate the creation, transporting, cutting, and merging of liquid droplets [108]. More recently, Aaron Wheeler's group at the University of Toronto has successfully demonstrated the culture of both non-adherent [109] and adherent mammalian [110] cells in a digital microfluidic format. Dielectrophoresis (DEP), the force applied to polar liquids in the presence of non-uniform electric fields, has also been utilized for digital microfluidics.…”
Section: Electrohydrodynamic Micropumpsmentioning
confidence: 99%
“…Devices used for imaging cells incorporated 0.8 Â 0.8 mm transparent windows (i.e., regions with no chromium) at the corners of some electrodes to assist with imaging. 44 Devices were assembled with an unpatterned ITO-glass top plate and a patterned bottom plate separated by a spacer formed from 2 pieces of double-sided tape (total spacer thickness 140 lm). To actuate droplets, driving potentials (200-250 V pp ) were generated by amplifying the output of a function generator (Agilent Technologies, Santa Clara, CA) operating at 18 kHz.…”
Section: Dmf Device Fabrication and Operationmentioning
confidence: 99%
“…38 DMF enables facile control over many different reagents for multi-step processes, a property that has been useful for enzyme assays 27,[39][40][41] and for applications involving cells. [42][43][44][45][46][47][48][49][50][51] In these initial applications, enzymatic bioreactors and cell culture and assays were implemented in homogeneous aqueous droplets manipulated by DMF. We propose that the marriage of DMF with hydrogels represents a welcome combination for forming miniaturized enzyme bioreactors and 3D cell culture scaffolds.…”
mentioning
confidence: 99%